Implementasi Load Balancing Menggunakan Algoritma Source IP Hash Pada Virtualisasi ESXi 7.0 Untuk Optimalkan Virtual Machine (Studi Kasus Pada Smk Angkasa 2 Sepatan Kab. Tangerang) - Haironi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In today's digital era, information and communication technology plays a very important role in the world of education. The increasing use of technology requires optimizing IT resources in schools in order to support an effective and efficient learning process. One workable solution is virtualization technology, which allows multiple operating systems or applications to run on the same physical machine. Virtualization has been widely applied in the business world to optimize the use of Server resources, and is now increasingly implemented in educational environments. In a virtualization environment, the Load Balancing technique can be used to manage workloads on multiple Virtual Machines running on the same host, so that virtual system performance can be improved. In this study, the implementation of the Load Balancing technique uses the Source IP Hash algorithm on the ESXi 7.0 virtualization platform at SMK Angkasa 2 Sepatan Kab. Tangerang, as a case study to improve performance in the school environment. SMK Angkasa 2 Sepatan Kab. Tangerang and got the results that with Load Balancing, the distribution of traffic load in each Virtual Machine becomes even, so that there is no downtime on the Server, and can optimize Server Management and reduce investment costs.